A galera da catedral : representações de um estilo de vida underground e lógicas de apropriação do espaço urbano - Silva, Williams Souza (2011)
The purpose of this master‟s thesis is to understand how the process of legitimization of underground‟s life style occurs. This life style is considered in this paper as one among several deviant life styles of Aracaju /SE. The conception of deviance used is Howard Becker‟ outsiders - it is considered as deviant the individual that is labeled as one. It refers to the ones who don‟t follow the established rule as contradicting the ones who have the power of classifying. The group studied here are the nocturne goers of Metropolitan Catedral‟s stairways in Aracaju. It is a heterogenic group that uses this space as a strategy of recognizing and demarcation of underground‟s life style. Therefore, the stairways served as the starting point of this thesis because they represent to the group the space with greater signification. However, the research did not limit itself to this space, once that one of the group‟s identity characteristic is the nocturne nomadism in the city‟s downtown. The methodological strategy used in the development of this thesis was to follow up the daily experiences of the group through the participative observation. This thesis is structured in three chapters. The first chapter, The undergrounds and Olímpio Campos Square: initial reflections about deviance and the space‟s appropriation in Aracaju. It has as objective to contextualize the research, to analyze the criterions of legitimization of underground‟s life style and to understand the process of choosing of the city‟s downtown as the locus of the group‟s actions. The second chapter Undergrounds‟ practices at Catedral Square, presents the underground group studied, its logics of appropriation and uses of the space mentioned. The third chapter, Catedral‟s people: trajections and identification and occupation‟s logics in the nocturne urban‟s space, emphasizes the two main characteristics of the group: the nomadism and its leisure options that give form to what is called underground‟s circuit of leisure.